AN ANALYSIS ON THE SPEAKING MATERIALS OF ENGLISH TEXTBOOK USED AT THE EIGHTH GRADE BASED ON CUNNINGSWORTH’S CRITERIA - Dewi Ernestia Simatupang; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
This study deals with the Cunningsworth’s criteria in speaking materials in Englishtextbook used at the eighth grade. The objective of this study was to determine whetherthe speaking materials in the English textbook "When English Rings A Bell" meet the 6criteria for evaluation by Cunningsworth such as aims and approaches, design andorganization, language content, speaking skill, topic, and methodology. The researchdesign of this study was descriptive qualitative. The data were analyzed qualitatively. Thefindings of this study are calculated based on each criterion separately. The findings showthat speaking materials of "When English Rings the bell" English textbook fulfills thecriteria of good textbook suggested by Alan Cunningsworth's checklist with fulfillment75% for aims and approaches, 60% for language content and 60% for Speaking Skill.These 3 criteria can be categorized as Fair. The other criteria, 80% for design andorganization, 83% for methodology and 100% for topic. These 3 criteria can becategorized as Good. So, the researcher can conclude that the speaking materials arepresented well enough with an appropriate oral presentation and practice of languageitems for students’ language level. In terms of speaking ability, this textbook greatlyassists students in understanding the materials given. In addition, format design includestitles, subheadings, and appropriate cross-referencing for ease of use.